Filming Nothingness: Invisibility, Ineffability, and the Inviolable Absence of God in Carmelo Bene’s Hamlet - Chillemi, Francesco (Mimesis Journal, 2015)
The paper aims to expound on the philosophical significance of Carmelo Bene’s oeuvre. In the 1970’s and 1980’s, when the international debate in Europe was dominated by French post-structuralism and Derridean deconstructive criticism, Beneian artistic praxis eluded – I contend – the so-called “metaphysics of presence.” First of all, I detect similarities and differences between the theoretical grounding of Bene’s works and Jacques Derrida’s and Giorgio Agamben’s respective philosophical inquiries into the essence of language. Subsequently, I analyze the distinctive stylistic techniques of the television film Amleto da Shakespeare a Laforgue (Hamlet from Shakespeare to Laforgue, 1974). A close attention is paid to the (dis)functions of linguistic and cinematic codes (such as verbal, body, and audiovisual language) and how they interfere with the construction of meaningful, consistent interpretations. Finally, I investigate the phenomenon of ineffability by drawing a parallel between mystical experiences and Beneian performances.